Fuzzy Model Predictive Controller for Artificial Pancreas - Mohamed El Hachimi; Abdelhakim Ballouk; AbdNaceur Baghdad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This work consists on new tuning of Model Predictive Controllers using Fuzzy Logic method. Tree relevant parameters are automatically adjusted the prediction horizon Np, the input weight R and the output weight Q. The proposed controller is implemented in an Artificial Pancreas and tested under realistic conditions in a commercial platform of simulation. The result of the simulations revealed the success of such a method to improve the controller’s performances compared to the previous ones.